2015
DOI: 10.1080/13548506.2015.1125007
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental motor skill, physical activity, and sedentary behavior in socioeconomically disadvantaged kindergarteners

Abstract: Guided by Stodden et al's conceptual model, the main purpose of the study was to examine the relation between fundamental motor skills (FMS; locomotor and objective control skills), different intensity levels of physical activity (light PA [LPA], moderate-to-vigorous PA [MVPA], and vigorous PA[VPA]), and sedentary behavior (SB) in socioeconomically disadvantaged kindergarteners. A prospective design was used in this study and the data were collected across the 2013-2014 academic school year. Participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 24 publications
3
37
0
8
Order By: Relevance
“…As preschoolers currently perform lower than recommended PA levels by increasing the associated health risk and compromising skill development and later school achievement, we suggest that, based on our results, children would spend more time in structured PA in kindergartens (Gu, 2016;Kippe and Lagestad, 2018;Kobel et al, 2019). Therefore, we suggest that this PEP could be adopted as an educational strategy to improve motor and pre-literacy skills in preschool children, known to be a peculiar growth period for the development of these characteristics.…”
Section: Discussionmentioning
confidence: 69%
“…As preschoolers currently perform lower than recommended PA levels by increasing the associated health risk and compromising skill development and later school achievement, we suggest that, based on our results, children would spend more time in structured PA in kindergartens (Gu, 2016;Kippe and Lagestad, 2018;Kobel et al, 2019). Therefore, we suggest that this PEP could be adopted as an educational strategy to improve motor and pre-literacy skills in preschool children, known to be a peculiar growth period for the development of these characteristics.…”
Section: Discussionmentioning
confidence: 69%
“…Stodden et al’s (2008) [ 51 ] conceptual model suggests that as children age, those with intermediate to higher levels of motor competence and greater PA levels will demonstrate higher performance scores in terms of both locomotor and object control skills [ 51 ], compared to those with less developed FMS. Literature supports the conceptual model [ 51 ], in that during the developmental stage (preschool years), the association between motor competency and PA is weak, but that developing FMS competency is important in reducing sedentary behaviour and increasing PA [ 22 ]. Preschool children with better-developed motor skills spend significantly more time in moderate to vigorous PA (MVPA) and significantly less time in sedentary behaviours, than children with less developed motor skills [ 59 ].…”
Section: Introductionmentioning
confidence: 94%
“…Stodden and colleagues [13] proposed a conceptual model indicating that developing sufficient FMS competence in childhood may increase the possibilities for children to engage in regular physical activity and influence the trajectory of childhood obesity. Cross-sectional studies support that children's FMS competence is associated with higher levels of physical activity [15], less sedentary behavior [16], higher cardiorespiratory fitness [14], and better weight status [17]. A recent systematic review also indicated that developing sufficient FMS allows children to function effectively and independently for their physical, social, and cognitive growth [18].…”
Section: Introductionmentioning
confidence: 98%